2019
DOI: 10.3390/en12152995
|View full text |Cite
|
Sign up to set email alerts
|

The Hierarchical Control Algorithm for DC Microgrid Based on the Improved Droop Control of Fuzzy Logic

Abstract: In the direct current (DC) microgrid composed of multiple distributed generations, due to the different distances between various converters and the DC bus in the system, the difference of the line resistance will reduce the current sharing accuracy of the system. The droop control was widely used in the operation control of the DC microgrid. It was necessary to select a large droop coefficient to improve the current sharing accuracy, but a too large droop coefficient will lead to a serious bus voltage drop an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The absence of a microgrid's centralized supervisor improves the strategy's dependability. Last but not least, the simulation outcomes support the suggested method [10]. Differences in line resistance between the different converters and the DC-bus in a direct current (DC) microgrid made up of numerous distributed generations degrade the current sharing accuracy of the system.…”
Section: Related Workmentioning
confidence: 59%
See 1 more Smart Citation
“…The absence of a microgrid's centralized supervisor improves the strategy's dependability. Last but not least, the simulation outcomes support the suggested method [10]. Differences in line resistance between the different converters and the DC-bus in a direct current (DC) microgrid made up of numerous distributed generations degrade the current sharing accuracy of the system.…”
Section: Related Workmentioning
confidence: 59%
“…When it comes to voltage regulation and load current sharing, traditional droop control inevitably creates a conflict. This study [10] suggested a hierarchical control algorithm based on the enhanced droop control of the fuzzy logic to resolve this issue. Improving the droop curve solved problems with voltage regulation and current distribution.…”
Section: Related Workmentioning
confidence: 99%
“…The level of impact may however be reduced by using lower size of droop coefficients. 55 Figure 9 demonstrates the synchronization of the three VISMAs on the grid at a unified system frequency. The transient and steady-state behaviors of the VISMAs are also illustrated, respectively, in Figures 10 and 11 for active and reactive power injections at the virtual buses.…”
Section: Model Extension With Externally Added Droopmentioning
confidence: 99%
“…The plot shows that voltage at the system buses is negatively impacted when external droop control is added. The level of impact may however be reduced by using lower size of droop coefficients 55 …”
Section: Validation Of the Proposed Algorithmmentioning
confidence: 99%
“…However, the lack of mature protection schemes is a huge obstacle for development of DC microgrids [4,5]. One of serious issues is the contradiction between the system protection and control caused by system structures.…”
Section: Introductionmentioning
confidence: 99%